Influence of Electronic Gadgets on the Formation of School Adulthood in Older Preschoolers - V. Koreneva, Vera; N. Lutoshkina, Viktoria; V. Maksimov, Sergei; P. Yatsenko, Mikhail; V. Rakhinskiy, Dmitriy (International Journal of Psychosocial Rehabilitation, 2020)
The paper deals with the development of intellectual readiness of children for school in the context of common computerization. The aim of the study is to determine the conditions under which electronic means can be used for the development of intellectual readiness for school in children of preschool age. The model of the organization of such development with the use of electronic means is described. On the basis of the theoretical analysis of psychological and pedagogical literature, this study considers the basic concepts like "readiness for school" and "intellectual readiness.". Intellectual readiness here is a structural element of general readiness for school, which in modern psychology and pedagogy is defined as a multicomponent education with three aspects of school readiness that are intellectual, emotional, and social readiness. The components of intellectual readiness to school are considered in the context of achieving the targets of the FSES PE that implies the development of differentiated perception, analytical thinking, rational memory, different approaches to knowledge, to reality, to the process of their logical acquisition through additional efforts, mastering the auditory perception of language, and the ability to understand and use symbols in preschoolers. The study identifies the conditions that ensure the development of intellectual readiness for school in the process of interaction between senior preschoolers and electronic means.